Acute cerebellar ataxia: a rare Toscana Virus (TOSV) meningoencephalitis complication. (3rd March 2020) - Suardi, Lorenzo Roberto; Di Lauria, Nicoletta; Pozzi, Marco; Rogasi, Pier Giorgio; Barilaro, Alessandro; Azzolini, Federica; Prestipino, Elio; Colao, Maria Grazia; Rossolini, Gian Maria; Bartoloni, Alessandro
Abstract: Purpose: Arbovirosis, viral infection transmitted by arthropods, is a widespread health problem. In Italy, as well for all Mediterranean basin, from late spring to the end of summer, Toscana Virus (TOSV), a sandfly borne virus, accounts for the majority of aseptic meningitis/meningoencephalitis cases. TOSV meningitis/meningoencephalitis has usually a self-extinguishing benign course. Our aim is to report a case of a young healthy women diagnosed with Toscana Virus meningoencephalitis with a complicated clinical course. Materials and methods/results: Case report of a 33-years old woman, admitted to the Infectious Diseases Unit at Careggi General Hospital (Florence-Italy), with a diagnosis of Toscana Virus meningoencephalitis. Seventy-two hours after the admission, she developed typical symptoms, as impaired legs coordination, slurred speech, stumbling and dysmetria, of acute cerebellar ataxia (ACA). Urgent neurological assessment was provided performing an electroencephalography study followed by a brain and brainstem magnetic resonance imaging. In the meanwhile, bilateral nystagmus arised. Through neurologist consultation ACA clinical diagnosis was then made and intravenous steroid therapy was administered with prompt symptoms resolution. The patient was finally discharged at day 10 since the ACA onset in good clinical conditions. Conclusions: To raise awareness among physicians about possible neurological complications during Toscana Virus meningoencephalitis